THE MASTER PLOT IN THE AUDIOVISUAL NARRATIVE. THE WESTERN CASE - José Félix GONZÁLEZ SÁNCHEZ (Fonseca, Journal of Communication, 2023)
A plot provides us the story that it offers a hyphen and later a film. Plots are limited, however possibilities, argument them that these offer music infinite. At the same time, we can say that all cultures avail themselves of some plots and similar arguments to structure their mythical stories.